Influence of Relationship Management Framework On the Performance of Supply Chain Management in Health Facilities in Nairobi Ciyt County, Kenya - Agango, Denis Ojung’a; Achuora, John (IJSSIT, 2018)
Purpose: the influence of relationship management framework on the performance of supply chain management in health facilities in Nairobi City County, Kenya.Materials and methods the study adopted a descriptive cross sectional survey research design the target population was 201 Health facilities in Nairobi City County as listed by Master Facilities List. The unit of analysis was Health facilities in Nairobi City County and the population frame was the entire list of 201 Health facilities as listed by Master Facilities List in Nairobi City County 2018. The unit of observation was supply chain management specialists. The study used both convenient sampling and stratified random sampling. The sampling size was computed based on the Yamane sampling size formulae. Primary data was collected through questionnaire. The questionnaire had both structured and unstructured questions. A pilot study was conducted to identify potential problem areas and deficiencies in the data collection instrument. Multiple regression models were used to analyse the data and establish the extent of association between the variables. Descriptive statistics such as frequencies mean and standard deviation was used to describe the data. Statistical package for social science (SPSS) (version 23.0) was used to facilitate data analysis. Results:The study established positive and significant relationship between Relationship Management Framework and supply chain performance. This implies that RMF enhances SCM performance of health facilities in Kenya is likely through collaborative relationship between stakeholders and operations of SCM. The study concludes that RMF significantly influence SCM practices Recommendations:The study recommendation that Supplier relationship framework activities such as: Value based compensation structure to vendors, Quality Assurance Teams to ascertain quality at source, Problem solving teams to address disputes, Training Framework and Long Term Contracts for mutual benefits necessitates a consistency of approach and a defined set of behaviours that foster trust over time.
Keywords: Relationship Management Framework; Quality Assurance Teams; Problem Solving Teams; Longterm Contracts; Training Framework; alue based compensation